2022
DOI: 10.1021/acs.jctc.1c00999
|View full text |Cite
|
Sign up to set email alerts
|

NMR Coupling Constants Based on the Bethe–Salpeter Equation in the GW Approximation

Abstract: We present the first steps to extend the Green’s function GW method and the Bethe–Salpeter equation (BSE) to molecular response properties such as nuclear magnetic resonance (NMR) indirect spin–spin coupling constants. We discuss both a nonrelativistic one-component and a quasi-relativistic two-component formalism. The latter describes scalar-relativistic and spin–orbit effects and allows us to study heavy-element systems with reasonable accuracy. Efficiency is maintained by the application of the resolution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

7
1

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 177 publications
3
44
0
Order By: Relevance
“…For completeness, we also note that in principle our method is not limited to TD-DFT, but can also be used within the Greens function based GW-Bethe-Salpeter equation framework. [36,37]…”
Section: Dft Implementationmentioning
confidence: 99%
“…For completeness, we also note that in principle our method is not limited to TD-DFT, but can also be used within the Greens function based GW-Bethe-Salpeter equation framework. [36,37]…”
Section: Dft Implementationmentioning
confidence: 99%
“…Also, while outlined for TD-DFT in this work, recent developments have shown that also the GW –Bethe–Salpeter equation method can be applied to solve eq 1 . 31 , 34 …”
Section: Methodsmentioning
confidence: 99%
“…91,92 Additionally, geometry gradients are implemented for meta-GGAs by extension of the existing machinery. 26,112 Furthermore, CDFT is available for the XC kernel of excitation energies from time-dependent density functional theory 95 (TD-DFT) and the contracted Bethe-Salpeter equation (cBSE), 113 NMR spinspin coupling constants, 74,75 as well as static, dynamic, and damped polarizabilities. 28 Additionally, the XC kernel is the only relevant DFT ingredient for NMR shieldings and shifts with a common gauge origin.…”
Section: Methodsmentioning
confidence: 99%
“…In this work, CDFT will therefore be applied to the self-consistent treatment of spin-orbit interaction and we study its impact on ground-state energies, excitation energies and magnetic resonance parameters. Besides calculations in strong magnetic fields and CDFT, the generalized kinetic energy density was applied to linear response theory for time-dependent density functional theory (TD-DFT), 68,69 electron paramagnetic resonance (EPR) spectra, 70,71 nuclear magnetic resonance (NMR) properties, [70][71][72][73][74][75] and magnetizabilities. 73 In all these approaches, the paramagnetic current density of the ground state was assumed to vanish.…”
Section: Introductionmentioning
confidence: 99%